A Career in Surgical Oncology: Finding Meaning, Balance, and Personal Satisfaction - Shanafelt, Tait (Springer-Verlag, 2007)
The practice of surgical oncology provides opportunities for both personal distress as well as personal satisfaction. While many surgical oncologists experience career burnout, others derive great meaning and satisfaction from their work. In this article, we review the literature on surgeon burnout, discuss potential personal and professional consequences, and consider steps individual surgeons can take to promote personal and professional satisfaction.